DETERMINATION OF THE BEST SOLVENT AND EXTRACT DURATION ON THE TECHNIQUE OF Gracilaria sp. MACERATION AS WELL AS ITS INFLUENCE ON MOISTURE CONTENT AND YIELD - Ismaningdyah Kurniawati; Maftuch Maftuch; Anik Martinah Hariati (Faculty of Science and Technology University Ibrahimy, 2016)
Gracilaria sp. is one type of red algae that has many benefits. It is widely used as a cosmetic, gelatin and medicinal materials. . In the fisheries, especially in the field of aquaculture, utilization of algae has been quite widely used. One of them is the use of red algae as a madicine ingredient and immunostimulant material to minimze the use of antibiotics in fish. Research on determination of solvent extraction and extract duration done to know the best of solvent extraction and extract duration used as a reference to determine the time of the maceration when the Gracilaria sp. extraction process. The appropriate solvent expected to produce high yield (results of extraction). The type of solvent used is ethanol 80%, ethanol 96%, acetone and aquades. The range of time that is used for the maceration is 24, 48 and 72 hours. The results showed that the best type of solvent is ethanol 96% with long soaking for maceration during 48 hours. The resulting yield is 0.9 with a moisture content of 10%.